Strategic Management of Islamic University in Integrating Science and Religion - Mohammad Ja'far As-Shodiq (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
This study aims to analyze the strategic management used by UIN Maulana Malik Ibrahim Malang in integrating science and religion, including formulation strategy, implementation process and evaluation conducted by the tertiary educational institutions. The method used is qualitative with descriptive analysis of case studies conducted in the field. The results of this study are divided into three. First, the formulation of strategies used by UIN Maulana Malik Ibrahim Malang includes the activities of making learning materials and applying integration in the daily behavior of the entire academic community. Second, strategy implementation is done by integrating Islamic values in the material, process and evaluation of learning. Third, strategy evaluation is carried out in two forms namely through the Employee Performance Target (SKP) and student satisfaction questionnaire.